Iran's Health Innovation and Science Development Plan by 2025 - B Larijani; R Majdzadeh; AR Delavari; F Rajabi; S Khatibzadeh; H Esmailzadeh; KB Lankarani (Tehran University of Medical Sciences, 2009)
"nBackground: Iran has made significant development in health and its scientific productivity, but a cohesive approach through a long-term plan is required to utilize knowledge for the country's health and development of health science and technology. As a part of a national agenda for development of "Comprehensive Scientific Map of the Country", the draft of the plan in the health-sector has been prepared."nMethods: A combination of two normative and exploratory approaches has been adopted to prepare the plan. For each part of the plan, a project defined. The group-projects developed their parts and consequently the draft of the plan developed. In the normative approach, the Islamic-Iranian values besides the country's vision for the year 2025 were assumed. National Innovation System concept used to analyze the related environment. Expert panels, using foresight methods, mainly prepared the information required for developing the plan. To finalize the plan, the draft was disseminated and receiving feedbacks, the document was polished appropriately."nResults: The long-term plan in the health sector has been prepared with the participation of around three-hundred experts. This plan includes vision, goals, monitoring and evaluation indicators, priorities, scenarios, policies, strategies, and requisites."nConclusion: The main challenges were as follows: considering equity in health, balance in choosing priorities (primordial and primary prevention against advanced technologies), and the role of the government in knowledge management.